Assessing current distribution and climate-driven potential invasion areas of Lycorma delicatula, with a focus on Taiwan - You-Sheng Lin; Jhih-Rong Liao (Biological Invasions, 2025)

A New Species of Fur Mite (Acari: Myobiidae) Parasitizing Laboratory Mice, With a Key to the Subgenus Myobia - Ying-Chien Cheng; Jhih-Rong Liao; Cho-Hua Wan (Acta Parasitologica, 2025)

Predicting habitat suitability for the Australian cycad-attacking weevil (Siraton internatus) under climate change - Yun Hsaio; Jhih-Rong Liao (Biological Invasions, 2024)
Cycads hold important economic and conservation value. Some species are extensively used in landscaping, while others are endangered and legally protected. The Australian cycad-attacking weevil, Siraton internatus , is notably destructive, occasionally causing infestations and invasions across various countries. This study simulated habitat suitability for S. internatus to assess its potential invasion and the impact of climate change. Habitat suitability was evaluated under current climate and four climate change scenarios over two time frames (2050 and 2090). Furthermore, we investigated the threat posed by S. internatus to cycad reserves, using Taiwanese reserves as a representative case. Our MaxEnt predictions demonstrated high accuracy, meeting multiple evaluation criteria. We explored the potential distribution of S. internatus within Australia and internationally, identifying suitable habitats in Africa, the Americas, Asia, and Europe. The case study highlighted the low habitat suitability within the two Taiwanese cycad reserves, which is projected to decrease to unsuitable levels under future climate change scenarios for this weevil species. Moreover, our results revealed that suitable habitat for S. internatus is projected to contract globally under all climate scenarios and time periods, but expansion in Chile and the southern Himalaya (e.g., Nepal). This study provides valuable insights into cycad conservation and pest invasion risks. The results support both global and local efforts to manage the invasion threats from this destructive Australian cycad-attacking weevil species. It also accentuates the urgency for continuous biosecurity inspections and prevention of exporting mature cycad caudexes from Australia.

To the knowledge of oribatid mites of the genus Nothrus (Acari, Oribatida, Nothridae) from Taiwan - Sergey G. Ermilov; Jhih-Rong Liao (Biologia, 2018)

Contribution to the knowledge of the oribatid mite genus Brassiella (Acari: Oribatida: Caloppiidae) - Sergey G. Ermilov; Jhih-Rong Liao (Biologia, 2017)